The effects of rice canopy on the air–soil exchange of polycyclic aromatic hydrocarbons and organochlorine pesticides using paired passive air samplers. (May 2015) - Wang, Yan; Wang, Shaorui; Luo, Chunling; Li, Jun; Ming, Lili; Zhang, Gan; Li, Xiangdong
Abstract: The rice canopy in paddy fields can influence the air–soil exchange of organic chemicals. We used paired passive air samplers to assess the exchange of polycyclic aromatic hydrocarbons (PAHs) and organochlorine pesticides (OCPs) in a paddy field, South China. Levels of OCPs and light PAHs were generally higher under the canopy than above it. We found that the rice canopy can physically obstruct the evaporation of most OCPs and light PAHs, and can also act as a barrier to the gaseous deposition of p, p' -DDT and heavy PAHs. Paddy fields can behave as a secondary source of OCPs and light PAHs. The homolog patterns of these two types of chemical varied slightly between the air below and above the rice canopy, implying contributions of different sources. Paired passive air samplers can be used effectively to assess the in situ air–soil exchange of PAHs and OCPs in subtropical paddy fields. Highlights: Effects of rice canopy on convection and diffusion of PAHs and OCPs were studied. Rice canopy can physically obstruct the emission of most OCPs and PAHs from soil. Paired passive air samplers can effectively assess field diffusion of PAHs or OCPs. Abstract : The paired passive air samplers are suitable to investigate the air–surface exchange of PAHs and OCPs in paddy fields.